Adsorpsi Ion Ca2+ Menggunakan Adsorben Silika GPTMS Termodifikasi Sulfonat - Putri, Reza Athia; Oktavia, Budhi; Alizar, Alizar; Parbuntari, Hesty (Departemen Kimia FMIPA UNP, 2024)
Silica is a metal oxide compound that is widely found in nature and is used as an adsorbent. Silica has the ability to adsorb ions because it has two groups of active sites that can be modified, namely siloxane (Si-O-Si) and silanol (Si-OH) groups. This modification was made to increase the ability of silica to absorb ions, one of which is the metal ion Ca2+. Silica modification was carried out by adding a bridging compound, namely glycidoxypropyltrimethoxysilane (GPTMS). The purpose of this research was to determine the optimum conditions of pH, contact time, and adsorption concentration of Ca2+ metal ions on sulfonate-modified GPTMS silica using batch method. The filtrate resulting from adsorption was analyzed using an atomic absorption spectrophotometer (AAS). The results showed that the optimum conditions for the adsorption of Ca2+ metal ions by sulfonate-modified GPTMS silica occurred at pH 5, contact time of 60 minutes, and concentration of 20 ppm. The adsorption process of Ca2+ metal ions by sulfonate-modified GPTMS silica follows the langmuir isotherm equation with an absorption capacity of 2.7824 mg/g. The results of the comparison of the absorption capacity of silica after modification obtained greater results than before modification, where the absorption capacity after modification was 2.225375 mg/g with an absorption percentage of 57.17%, before modification the absorption capacity was 1.677275 mg/g, and the absorption percentage was 43.07%.